FUTURE ENGLISH LANGUAGE TEACHERS’ LIFE SKILLS DEVELOPMENT IN METHODOLOGY COURSE - Konovalenko, Tetiana; Goncharova, Olga (Studies in Comparative Education, 2018)
The article is devoted to the issues of future English language teachers’ life skills development. The authors prove the topicality of life skills development and their role in the professional competence of a teacher. It is stated that there are no researches on the whole complex of life skills in the methodological bank of a teacher. The skills under consideration are as follows: intercultural awareness, communicative skills, teamwork skills, time management skills, critical thinking skills, ability to solve problems, information literacy skills, creativity. In the article the experimental course of English Language Teaching Methodo-logy is presented as the one which is crucial in future teachers’ professional educa-tion. The sessions within the experimental curriculum help students to develop their life skills. The results of methodological experiment presented in the article emphasise its connection with contemporary requirements to the teacher pro-fessional competence in general and according to the Concept of New Ukrainian School in particular.